Development of a practical biocatalytic process for (S)-N-Boc-3-hydroxypiperidine synthesis. Issue 16 (19th April 2017) - Chen, Li-Feng; Fan, Hai-Yang; Zhang, Yi-Ping; Wu, Kai; Wang, Hua-Lei; Lin, Jin-Ping; Wei, Dong-Zhi
Graphical abstract: Highlights: A carbonyl reductase was discovered to reduce NBPO to ( S )-NBHP with high activity. The product ( S )-NBHP was the main inhibitor for the reaction. An ethyl caprylate-water biphasic system was used to alleviate product inhibition. NBPO at 1200 mM was completely reduced to ( S )-NBHP (>99% ee ) within 6 h. Abstract: ( S )- N -Boc-3-hydroxypiperidine (( S )-NBHP) is an important chiral intermediate for the synthesis of ibrutinib, an anticancer drug targeting B-cell malignancies. An NADPH-dependent reductase (YDR541C) from Saccharomyces cerevisiae was isolated and found to show excellent catalytic activity in the production of ( S )-NBHP. The reductase YDR541C was cloned and overexpressed in Escherichia coli BL21 (DE3), purified to homogeneity, and its catalytic properties were studied. Furthermore, an ethyl caprylate-water (1:1, v/v) biphasic system was introduced to alleviate product inhibition. After optimization of the reaction, as much as 1200 mM N -Boc-piperidin-3-one (NBPO) (240 g/L) was asymmetrically reduced to ( S )-NBHP within 6 h, resulting in a yield of 99%, an enantioselectivity of >99.5% ee, and a total turnover number (TTN) of 8000. These results indicate great potential for industrial application.